2016
DOI: 10.1007/s00234-016-1765-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinical validation of synthetic brain MRI in children: initial experience

Abstract: Diagnostic accuracy and quality of synthetically generated sequences are comparable to conventionally acquired sequences as part of a standard pediatric brain exam. Further confirmation in a larger study is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 15 publications
1
38
0
Order By: Relevance
“…It could be shown that contrasts generated by SyMRI were not inferior to those of conventionally acquired contrasts [15]; however, there are still few data on the use of this software in children and neonates. West et al applied this technique in a cohort of 32 patients with a mean age of 12.6 years [38]. Furthermore, there are descriptions of the use of SyMRI in a cohort of 29 patients with a median age of 6 years [39].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It could be shown that contrasts generated by SyMRI were not inferior to those of conventionally acquired contrasts [15]; however, there are still few data on the use of this software in children and neonates. West et al applied this technique in a cohort of 32 patients with a mean age of 12.6 years [38]. Furthermore, there are descriptions of the use of SyMRI in a cohort of 29 patients with a median age of 6 years [39].…”
mentioning
confidence: 99%
“…Primarily in adults, the quality of SyMRI-generated images appears to be equal to that of conventional MRI sequences [15]. Also, in a pediatric cohort, there is evidence that the quality of the images was not inferior to conventionally acquired MR contrasts [38]. Interestingly, Andica et al reported that fluid-attenuated inversion recovery (FLAIR) contrasts generated by SyMRI were even superior in the diagnosis of neonatal meningitis compared to conventional FLAIR sequences [44].…”
mentioning
confidence: 99%
“…The axial QMAP sequence (4-mm section thickness, 1-mm gap, matrix size of 320 ϫ 256, acquisition time of 6 minutes) was included as an optional sequence (when time allowed) and has been described previously. [7][8][9] The algorithm for subject inclusion is shown in Fig 1. Studies with abnormal findings on clinical radiology reports were excluded. A systematic medical chart review was performed on the remaining 266 examinations to exclude those with clinical diagnoses or medications potentially affecting intracranial tissue volumes ( Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…7 Fully automated synthetic MR imaging visualization software loads the raw DICOM data, performs relaxivity curve fitting to the Bloch equations, and calculates wholebrain R1, R2, and PD maps used to synthesize MR images with standard contrast. [7][8][9] Additionally, the R1, R2, and PD maps are used as input to calculate an intracranial mask that determines the intracranial volume (ICV). A look-up table is used to convert R1, R2, and PD values of each voxel into tissue volume fractions with no atlas, manual tracing, or a priori assumptions of tissue distribution or anatomy.…”
mentioning
confidence: 99%
See 1 more Smart Citation